Problematika Peran MGMP dalam Implementasi KMA 183 dan KMA 184 Tahun 2019 - Elfa Tsuroyya (Lembaga Sosial Rumah Indonesia, 2021)
The subject of Islamic Cultural History undergoes many curriculum changes that continue to move dynamically. One of these changes is the emergence of KMA 183 and KMA 184 in 2019. This article aims to reveal the problems faced by MGMP SKI MA DIY in implementing KMA 183 and KMA 184 in 2019. Qualitative research with descriptive-analytical methods is the type of research used. Data analysis using analytic-qualitative type. The research location was taken in Yogyakarta with the subject of MGMP SKI MA DIY having its address at PSBB MAN 3 Sleman Jl. Magelang KM 3.5 Sinduadi Mlati Sleman Yogyakarta. Structured interviews, documentation and observation carried out the data collection technique. A triangulation test is used to ensure the reliability of the data obtained. The results showed that the problems faced by teachers in the learning process were divided into three aspects: problems in socializing policy implementation, problems in implementing policy implementation, and problems in monitoring policy implementation.